2021
DOI: 10.36863/mds.a.17212
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Food Supply Chain

Abstract: Hospital is a complex supply chain made up of multiple structures, stakeholders, operations, as well as information and material flows. Due to the Covid-19 pandemic, hospital overcomes several major challenges these last few months, which leads to consider its supply chain digitalization as a priority to improve healthcare and hospital services quality. Interesting in the specific service of hospital food, this article asks: How does digitalization support hygiene requirements in the hospital food supply chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…No women have received training on good hygiene and manufacturing practices (GHMP). Difficulties related to non-compliance with GHMP may be due to a lack of information, training, qualification, and awareness [5] , [30] , [31] , [32] , [33] , [34] , [35] , [36] . In addition, the storage conditions of raw materials and prepared food have shown that only in one private school refrigeration is used to preserve unsold prepared food.…”
Section: Discussionmentioning
confidence: 99%
“…No women have received training on good hygiene and manufacturing practices (GHMP). Difficulties related to non-compliance with GHMP may be due to a lack of information, training, qualification, and awareness [5] , [30] , [31] , [32] , [33] , [34] , [35] , [36] . In addition, the storage conditions of raw materials and prepared food have shown that only in one private school refrigeration is used to preserve unsold prepared food.…”
Section: Discussionmentioning
confidence: 99%
“…No women have received training on good hygiene and manufacturing practices (GHMP). Difficulties related to non-compliance with GHMP may be due to a lack of information, training, qualification, and awareness [5,[30][31][32][33][34][35][36]. In addition, the storage conditions of raw materials and prepared food have shown that only in one private school refrigeration is used to preserve unsold prepared food.…”
Section: Discussionmentioning
confidence: 99%